Bilateral simultaneous central retinal vein occlusion secondary to trauma - Debnath, Purabi Rani; Bhowmik, Narayon Chandra; Debnath, Dilip Kumar; Sarker, Sujit Kumar (Bangladesh Medical Journal, 2014)
Retinal vein occlusion refers to the closure of the central retinal vein that drains the retina or to that of one of its branches. Central retinal vein occlusion (CRVO) is caused by age related changes in the retinal vessels. Bilateral CRVO is a relatively rare event. Only less than 10% cases are bilateral, simultaneous bilateral CRVO is very rare. We are presenting a case report regarding a middle aged patient with history of trauma who presented with bilateral CRVO in the depatment of ophthalmology, BIRDEM General Hospital, Dhaka. After detailed clinical work up and invesigation a diagnosis of bilateral CRVO secondary to trauma was made. DOI: http://dx.doi.org/10.3329/bmj.v43i1.21377 Bangladesh Med J. 2014 January; 43 (1): 33-35